2010
DOI: 10.1007/s10571-010-9549-1
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexia-Associated Kiaa0319-Like Protein Interacts with Axon Guidance Receptor Nogo Receptor 1

Abstract: To identify the putative interacting partners for Kiaa0319-like protein. KIAA0319-like, located near the dyslexia susceptibility locus, DYX8 in chromosome 1p34.3, has been suggested as a positional candidate for developmental dyslexia due to its homology with another gene, KIAA0319 which has been strongly established as a candidate gene for developmental dyslexia. Previous research has shown that a single marker, rs7523017 (P = 0.042) has been associated with developmental dyslexia by a Canadian group. There i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Transgenic over-expression of Grin2b in the forebrain of mice and in the cortex and hippocampus of rats results in an increased activation of the NMDA receptors, with mice and rats displaying a superior performance in various tests of learning and memory (Tang et al 1999;Wang et al 2009). Moreover, functional studies revealed that DYX1C1, KIAA0319, and GRIN2B genes are likely involved in neuronal migration and axon growth (Szalkowski et al 2011(Szalkowski et al , 2012Ito et al 1997;Cull-Candy et al 2001;Kim et al 2005;Wang et al 2006;Rosen et al 2007;Akashi et al 2009;Velayos-Baeza et al 2010;Peschansky et al 2010;Currier et al 2011;Poon et al 2011), which is in turn consistent with the original neuroanatomical finding of focal architectonic dysplasias and neuronal ectopias in brains of people with DD (Galaburda and Kemper 1979;Galaburda et al 1985) as well as with the recently proposed theoretical molecular network involved in neuronal migration and neurite growth for DD (Poelmans et al 2011). In particular, signaling through the network can be initiated at the neuronal cell membrane where the KIAA0319 proteins may function as receptors for netrin-like molecules-which regulate the direction and rate of axon/neurite outgrowthand in the direct adhesion between neurons and glial fibers during neuronal migration (Poelmans et al 2011).…”
Section: Discussionsupporting
confidence: 79%
“…Transgenic over-expression of Grin2b in the forebrain of mice and in the cortex and hippocampus of rats results in an increased activation of the NMDA receptors, with mice and rats displaying a superior performance in various tests of learning and memory (Tang et al 1999;Wang et al 2009). Moreover, functional studies revealed that DYX1C1, KIAA0319, and GRIN2B genes are likely involved in neuronal migration and axon growth (Szalkowski et al 2011(Szalkowski et al , 2012Ito et al 1997;Cull-Candy et al 2001;Kim et al 2005;Wang et al 2006;Rosen et al 2007;Akashi et al 2009;Velayos-Baeza et al 2010;Peschansky et al 2010;Currier et al 2011;Poon et al 2011), which is in turn consistent with the original neuroanatomical finding of focal architectonic dysplasias and neuronal ectopias in brains of people with DD (Galaburda and Kemper 1979;Galaburda et al 1985) as well as with the recently proposed theoretical molecular network involved in neuronal migration and neurite growth for DD (Poelmans et al 2011). In particular, signaling through the network can be initiated at the neuronal cell membrane where the KIAA0319 proteins may function as receptors for netrin-like molecules-which regulate the direction and rate of axon/neurite outgrowthand in the direct adhesion between neurons and glial fibers during neuronal migration (Poelmans et al 2011).…”
Section: Discussionsupporting
confidence: 79%
“…KIAA0319 has a role in appropriate adhesion between migrating neurons and radial glial fibers and may also regulate growth and differentiation of dendrites in the developing brain [97-99]. The gene has four polycystic kidney disease domains with homology to the extracellular domains of the PKD protein PKD1, which are involved in cell-adhesive functions [100].…”
Section: Resultsmentioning
confidence: 99%
“…The function of this gene has not been completely characterized, although there is evidence that KIAA0319L interacts with the axon guidance protein Nogo receptor 1 (NgR1). This finding, combined with the fact that these proteins interacted in cortical neurons in vitro , suggested that KIAA0319L may participate in axonal guidance in the cerebral cortex (Poon et al, 2011a). Subsequent work in mice found that Kiaa0319L was localized to layers 4 and 6 of cerebral cortex, but also to most of the hippocampus, the molecular layer (and occasional Purkinje cells) of the cerebellum, thalamus, and olfactory bulb (Poon et al, 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…Although the specific function of KIAA0319L is unknown, it has been shown to interact with Nogo receptor 1, an axon guidance protein (Poon et al, 2011a) that is similar to ROBO1 , a CDSG on the DYX5 locus (Nopola-Hemmi et al, 2001, Hannula-Jouppi et al, 2005), which has been shown to modulate axon guidance and neuronal migration (Wong et al, 2001, Hivert et al, 2002, Gonda et al, 2012). In the mouse brain, Kiaa0319l is expressed in both astrocytes and neurons, most strongly in the olfactory bulb, hippocampus, and neocortex (Poon et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%